Biologics: An Update and Challenge of Their Pharmacokinetics - Shi, Shaojun (Current Drug Metabolism, 2014)
Biologics, including but not limited to monoclonal antibodies (mAbs), cytokines, growth factors, enzymes, hormones, vaccines, antibody fragments (e.g. Fabs), and antibody drug conjugates (ADCs), have a powerful clinical impact on the management of a wide variety of diseases. When compared to small molecules (SMs), they have different physicochemical properties and demonstrate unique and complex pharmacokinetic (PK) characteristics that are dependent on several factors such as net charge, neonatal Fc receptor [FcRn], Fcγ receptor [FcγR], glycosylation, PEGylation or aggregation. While PK principles are consistent, the underlying mechanisms that determine processes of absorption, distribution, metabolism, and excretion (ADME) of biologics are quite different from those of SMs. Furthermore, the immunogenicity, especially formation of anti-drug antibody (ADA) and cellular immune responses, may play an important role in their PK. Investigating the drug interaction (DI) potentials of biologics is inherently complicated, and the most well documented DI mechanism involves cytokine-mediated changes in drug-metabolizing enzymes. Population PK (Pop-PK) analyses have been successfully applied in assessing covariates in the disposition of biologics. The mechanism-based (target-mediated drug disposition [TMDD]) and physiologically based PK (PBPK) models are applied to predict PK characteristics of biologics. Developing a validated bioanalytical assay (mass assay, activity assay and immunogenicity assay) is critical in determining the PK properties of biologics. In this review, we will highlight the current knowledge, as well as the challenges around the PK-related issues in optimization of drug development and clinical practice of biologics.
Keywords: pharmacokinetic drug interactions